Ecological and construct validity of a repeated sprint test in male youth soccer players - Fernandes-Da-Silva, J.; Castagna, C.; Teixeira, A. S.; Carminatti, L. J.; Francini, L.; Póvoas, S. C. A.; Antonacci Guglielmo, L. G. (The Journal of Strength and Conditioning Research, 2021)
This study aimed to examine the relationship between a repeated sprint ability (RSA) test (5 bouts of 30-m sprints interspersed by 30 seconds of recovery) and match-related physical performance in male youth soccer players. Although 60 outfield players were evaluated, only data from players who participated in the full matches (n = 39) were retained (8 central defenders, 7 external defenders, 8 central midfielders, 8 external midfielders, and 8 forwards). To verify the ecological validity of this RSA protocol, the association between the best (RSAbest) and mean (RSAmean) sprint time in the 5 × 30-m and physical match performance during friendly youth soccer games was examined. Physical match demands were assessed using global positioning system technology (10 Hz) considering distance covered in selected arbitrary speed categories. The absolute speed thresholds were the same for all the players. Players were categorized into 2 groups based on the 5 × 30-m performance: RSAmean times below (i.e., faster) and above (i.e., slower) the median value. Players with faster RSAmean times covered significantly more distance sprinting during friendly matches (606 ± 204 m, +47.0%; t = 4.953; effect size = 1.88, 1.24; 2.52, p = 0.001) compared to their slower counterparts (322 ± 145 m). A large negative correlation (r = -0.63, -0.77; -0.44, p = 0.001) was found between RSAbest time (4.59 ± 0.27 seconds) and match sprint distance (457 ± 229 m). Likewise, RSAmean time (4.76 ± 0.25 seconds) was also largely associated (r = -0.60, -0.75; -0.39; p = 0.001) with in-game sprinting performance. The results of this study provided evidence to support the construct and ecological validity of the 5 × 30-m protocol in male youth soccer players. Furthermore, differences in 5 × 30-m performance explained the amount of sprinting activity performed during the match.